Impact of digitalisation on the employment structure and labour market in the Russian Federation - A. V. Mukhanov (Цифровая социология)
The article attempts to summarise existing points of view on the issues of assessing the impact of digitalisation on the employment structure and the labour market in the Russian Federation (here inafter referred to as RF). The purpose of the study is to identify the key areas of the impact of digitalisation on socio-economic processes, the employment structure and the labour market in the RF. General scientific research methods are used: analysis, synthesis, comparison, generalisation, bibliographic description as well as the method of graphical visualisation of data. Various components of the impact of digitalisation and digital technologies on employment are analysed. Both positive and negative impacts of digitalisation are noted. Changes in the nature of work activity are considered, a natural increase in demand for digital competencies of employees is noted, the processes of emergence of new professions and forms of employment, especially non-standard forms, are determined. Conclusions are made about the versatility and inconsistency of the impact of digitalisation on the labour market; digitalisation creates both significant prospects for improving employment (new professions, promotes growth in labour productivity and efficiency, allows for the development of remote and flexible forms of employment) and necessitates the development of a number of problematic issues (the need for constant updating and development of workers’ skills, especially in the area of digital competencies, increasing complexity of labour, polarization of the labour market, regulation of non-standard forms of employment)